2007
DOI: 10.1111/j.1365-2141.2007.06674.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytosis in polycythaemia vera predicts both inferior survival and leukaemic transformation

Abstract: highlighted the prognostic relevance of leucocytosis on various aspects of the disease in PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 32 publications
(42 reference statements)
8
115
0
Order By: Relevance
“…[69][70][71][72] By contrast, a leukemogenic potential of hydroxyurea (HU) has not been shown in clinical trials, although there is evidence showing that the sequential use of HU and other cytoreductive drugs (alkylating agents, radioactive phosphorus) increases the risk of AL/MDS. [72][73][74][75] In addition, several retrospective studies did not find an increased risk of AL in PV and ET treated with HU alone, [76][77][78] and similar conclusions were drawn from a recent meta-analysis of HU therapy in sickle cell anemia. 79 Still, very long-term results of prospective studies in HU-treated MPN patients with more than 10 years of follow-up showed a cumulative incidence of AL/MDS of more than 10% beyond 12 years of follow-up, suggesting that the risk of leukemic evolution could be higher than reported earlier in studies with shorter follow-up.…”
Section: Ifn-a and Leukemic Evolutionsupporting
confidence: 51%
“…[69][70][71][72] By contrast, a leukemogenic potential of hydroxyurea (HU) has not been shown in clinical trials, although there is evidence showing that the sequential use of HU and other cytoreductive drugs (alkylating agents, radioactive phosphorus) increases the risk of AL/MDS. [72][73][74][75] In addition, several retrospective studies did not find an increased risk of AL in PV and ET treated with HU alone, [76][77][78] and similar conclusions were drawn from a recent meta-analysis of HU therapy in sickle cell anemia. 79 Still, very long-term results of prospective studies in HU-treated MPN patients with more than 10 years of follow-up showed a cumulative incidence of AL/MDS of more than 10% beyond 12 years of follow-up, suggesting that the risk of leukemic evolution could be higher than reported earlier in studies with shorter follow-up.…”
Section: Ifn-a and Leukemic Evolutionsupporting
confidence: 51%
“…It is not clear whether leukocytosis, which is seen in certain MPN patients and which appears to be associated with certain complications or evolution toward leukemia, 102 may be due to the pathologic activation of G-CSFR by JAK2 V617F. Granulocytes from patients with MPNs presented altered gene expression promoted by JAK2 V617F expression and confirmed a recapitulation of cytokine receptor signaling, resembling profiles of granulocytes activated by G-CSF.…”
Section: Spotlightmentioning
confidence: 95%
“…It can be noted that for this receptor, a very delicate balance has been identified between the activation of STAT3, required for differentiation and inducing a stop in cell growth (necessary for differentiation), and STAT5, which promotes proliferation. 102 Binding of SOCS3 through its SH2 domain to a phosphorylated tyrosine residue in the receptor's cytosolic end specifically downregulates STAT5 signaling. Deletion of the cytosolic region, which contains the binding site for SOCS3, leads to enhanced STAT5-to-STAT3 signaling ratio, 102 and this is associated with evolution toward acute myeloid leukemia of patients with severe congenital neutropenia.…”
Section: Spotlightmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-polycythemia vera myelofibrosis (post-PV MF) is a long term clinical outcome in around 10 % of patients with polycythemia vera (PV) [1,2]. No clear risk factors have been identified for such a transformation.…”
Section: Introductionmentioning
confidence: 99%